(3eLQHGJ GdCJbjGA ef Ydhe GdChdjGAs - (3YHO GdeLjO GdeUQjs
(3ChdgG (B:s
(3hHYO , aEf GdYde GdCQhGM hGdCSQGQ heYOf GdaVd hGdEjKGQ hGdPNQ efg ddOGQ GdCNQI NjQ OGQ ddSjGQ s
(3BNQgG (B:s
,(3Gddg JYGdi GdeYWi GdhgGH agPG gh GdEcSjQ GdCcHQ aGYde Pdc hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B284 - (3U(B290s
(3GdfSNI HgG MhGTs
(3jdi Pdc (B: (3dGMbI ef (B[ (3cJGH(B] (3QGMI GdCQhGM hgj ai UaI ENQGL RjHb GdMLQ GdecQe hZjQ Pdcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B180 s
Keywords: (3GdcjejGA h GdWHjYjGJs